System Diagnostics and Monitoring applied in Flaws of the Structure Systems in HPSs by Using Image Processing - Thomazella, Rogerio [UNESP]; Cogo Castanho, Jose Eduardo [UNESP]; Franchin, Marcelo Nicoleti [UNESP]; Algarve, Richard Jose [UNESP]; Lofrano Dotto, Fabio Romano [UNESP]; Fiocchi, Arthur Alves [UNESP]; Fernandes, Valdir; Carvalho Freitas Filho, Italo Tadeu; Nunes, Mauricio; IEEE (Ieee, 2015)
The system proposed in this work makes use of an underwater operated vehicle to replace the divers in the inspection operation in Hydroelectric Power Station (HPS) equipped with high-resolution video cameras, able to get sharp and clear images for the embedded system processing. Additionally the images can be seen, enhanced and recorded in the control system. The use of image processing and intelligent systems techniques increases the reliability of the diagnosis. The proposed system presents numerous operational advantages allowing the replacement of the inspection teams, reducing the human risk element for the workers involved and reduces costs. The equipment could be used, repeatedly, in numerous similar activities and tasks. The implementation of the proposed system has been a resource for significant reduction in inspection and operating costs, giving a quick return on investment.
Keywords: Power plant monitoring; preventive maintenance; turbine inspection; image processing; ROV